Hiperuricemia como factor asociado a mortalidad intrahospitalaria en pacientes con síndrome coronario agudo atendidos en el Hospital Víctor Lazarte Echegaray - Mendoza Briones, José Napoleón (2019)
Introduction: Uric acid is a metabolite from the degradation of purine bases. Its abnormal serum concentration is a signal of alterations in its metabolism, it is usually elevated in subjects with risk factors for cardiovascular disease such as in acute myocardial infarction, in which there is sudden and abrupt interruption of coronary arterial flow, generally related to Acute thrombotic phenomena associated with coronary lesions due to atherosclerotic plaques. Objective: To demonstrate whether hyperuricemia is a factor associated with in-hospital mortality in patients with acute coronary syndrome treated at the Víctor Lazarte Echegaray Hospital. Method: This study corresponds to an analytical, observational, retrospective, case-control design. In which the population was divided into: cases (deceased SICA) and controls (SICA survivors) and analyzed how many had hyperuricemia in each of them. Conclusion: Hyperuricemia is a factor associated with in-hospital mortality in patients with acute coronary syndrome.